Enhancing Teachers' Proficiency in Implementing Augmented Reality Technology as Interactive Learning Media - Lativa Mursyida; Fadhli Ranuharja; Ika Ika Parma Dewi; Agariadne Dwinggo Samala Agariadne Dwinggo Samala; Ryan Fikri Ryan Fikri; Randi Proska Sandra Randi Proska Sandra; Efrizon Efrizon (CONSEN: Indonesian Journal of Community Services and Engagement, 2023)
Creativity is critical in education, especially for teachers in crafting instructional media that captivates and engages students' interest in comprehending the subject matter. Each student possesses distinct interests and enthusiasms towards the instructional press, allowing educators to innovate in devising captivating learning resources. One form of instructional media that offers a unique experience is augmented reality (AR) based media, which delivers individualized audio-visual interactions and experiences. In this research, we harness the Assemblr Edu platform, an AR and VR-based instructional media tool, within a community engagement workshop held at SMPN 3 Batusangkar, involving participation from educators of the Natural Sciences Teachers' Subject Study Group (MGMP IPA) in Tanah Datar Regency. The research aims to enhance the creative aptitude of educators in designing instructional media using the augmented reality technology of Assemblr Edu. Employing a quantitative approach, we gauge the extent of success among educators in crafting interactive instructional media using the Assemblr Edu platform, yielding augmented reality instructional media accessible through Android smartphones. The research findings underscore that Assemblr Edu, integrated with augmented reality technology, remarkably stimulates students' interest, amplifies their learning motivation, and assists them in comprehending subject matter while efficiently tackling assignments